A qualitative study of factors influencing the utilization of institutional delivery: Insights from pastoral communities, Southwest Ethiopia - Kindie Kebede; Andualem Henok Tadesse; Bayu Bekele (Mashhad University of Medical Sciences, 2020)
Background & aim: The practice of institutional delivery services utilization is reported to be very low in Ethiopian pastoral community. In this regard, health programmers should gain an insight into factors influencing the utilization of institutional delivery to improve health facility delivery among these women. Methods: A qualitative study was conducted in pastoralist communities of Bench-Maji zone, southwest Ethiopia within September-October 2017. The data were collected through in-depth interviews and focus-group discussions with women, health extension workers, traditional birth attendants, and supervisors of health extension workers. After transcription and translation, the data were thematically analyzed using Open Code software (version 3.6). Results: As evidenced by the results of the current study, poor risk awareness, inadequate infrastructure and transport, poor quality of care, and lack of financial independence hinder easy access to obstetric care. In this regard, readily available traditional birth attendants become the best alternative to the non-responsive health system. These communities were also marginalized since they receive less health education due to their long distances to healthcare facilities. Consequently, they are encouraged to deliver at home in the belief that only complications require medical attention. Conclusion: In order to design interventions to support pastoral women's use of obstetric services, existing barriers need to be addressed together since they jointly hinder women's access to institutional delivery.